Epidemiology and pattern of paediatric trauma in one of the biggest trauma centres of India - Kunwar, Abhijeet; Manjhi, Birju; Saurabh, Anand; Shekhar, Shubhanshu (International Journal of Research in Orthopaedics, 2020)
Background: The objective of the study was to assess the epidemiology and pattern of trauma in paediatric patients coming to a tertiary care trauma centre in Purvanchal region of country. Methods: Study was conducted at Trauma Centre, Institute of Medical Sciences, BHU. A retrospective data was collected from the emergency entry record book for the paediatric patients coming to emergency with trauma from January to December 2018. A total of 328 patients were included in study. Patient with accidental hanging and those of sexual assault and drowning were not taken in study. Results: Patients in the age group of above 6 years were most numerous 61%. Boys were more commonly injured then girls of same age group with M: F being 1.4:1. Fall was the most common mode of injury overall 45.12% and for the children below 6 years of age 63%. However, RTA was the most common cause in children of above 6 years age group 40.5%, closely followed by fall. Home was found to be the most common location of injury. Females outnumbered males in case of assault injury (7 of 12). Musculoskeletal injury was most common 42%, head injury 27%, polytrauma 12%, while superficial injuries in form of abrasion, contusion etc were 19%. Of all 42% were taken inpatient, 50% discharged on OPD basis and 8% went LAMA. Conclusions: Most of the times the paediatric traumas occur in foreseeable circumstances, most of them occurring at home or around it suggesting the need for more supervision during playing and identification of specific risk factors for these injuries in our setting. Planning of strategies should be according to the epidemiological trends.